Instagram as a Promotional Media for Islamic Boarding School Darul Ilmi Wal Amal - Retnosary, Rieke; Yanti, Erna Diana; Triana, N. Neni; Kusumah, Deden Santa Winata; Prayodo, Gito; Tuhagana, Aji (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: This study examines how Instagram can be optimized as a promotional tool for Pesantren Darul Ilmi wal Amal, an Islamic boarding school with limited public visibility and student enrollment. The research addresses the challenge of promoting a newly established educational institution through effective digital channels. Method: Employing a qualitative approach, the research involved stakeholder discussions to map promotional strategies, development of Instagram content showcasing institutional profiles and activities, and evaluation using open-ended questionnaires distributed via Google Form. Practical Applications: The findings provide actionable recommendations: enhancing visual quality and consistent branding, creating emotionally engaging stories, utilizing interactive features (polls, Q&A), posting educational content, optimizing captions and hashtags, and using analytics to refine engagement strategies. Conclusion: While the initial Instagram presence was visually appealing, it lacked structured planning and engagement. With strategic content optimization and consistency, Instagram demonstrates significant potential as an effective promotional medium to increase public interest and student enrollment in the Islamic boarding school.